Critical nitrogen dilution curve in processing potato cultivars - Giletto, Claudia Marcela; Echeverria, Hernan Eduardo (Scientific Research, 2018)
The critical nitrogen dilution curve (CNDC) can be used as a diagnostic tool to assess crop N nutrition during the growing season. Potato cultivars have different biomass production and accumulation of N and consequently different growth patterns. These differences among cultivars may result in different CNDC. The aims were a) to determine the CNDC for different potato cultivars; b) to compare these curves with reference curves; and c) to assess the possibility of using the CNDC to estimate the N nutritional status of the crop. The biomass production and N concentration of shoots and tubers of potato cultivars Innovator, Gem Russet, Umatilla Russet, Bannock Russet and Markies Russet were measured. The harvest index (HI) and N harvest index (NHI) were determined. The coefficient a of the CNDC was similar among cultivars, while the coefficients b for Innovator and Gem Russet (-0.42 and -0.36, respectively) were smaller than those for the other cultivars (average -0.25). HI and NHI were greater in Innovator, smaller in Markies Russet, and intermediated in the other three cultivars. The coefficients b of the CNDC were correlated with HI and NHI (HI, r = -0.62, p < 0.0001 and -0.53, p < 0.0001; NHI, r = -0.60, p < 0.0001 and -0.61, p < 0.0001 for 2004/5 and 2005/6, respectively). The relationship between relative tuber yield (RY) and N nutrition index (NNI) was fit by a quadratic-plateau function. At similar situations of N deficiency, Innovator had lower yield and greater response to N rate than the other potato cultivars. The differences in HI and NHI among cultivars may explain the differences in the coefficient b of the CNDC. The NNI identified the status of N adequately in potato cultivars.